Implementasi Program Keluarga Harapan (PKH) dalam Mengentaskan Kemiskinan di Desa Bantang, Kecamatan Kintamani, Kabupaten Bangli - Surya Ningrat, Ida Bagus Gde Krisna; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2019)
ABSTRACT Hope for Families Program is a social protection program in the form of cash aid given to very low- income household along with a series of responsibility to fulfill. The problem that occurred in the implementation of this program in Bantang village are inadequate update on the poor-family database, and some difficulty in carrying out monthly gathering with the program recipient thus decreasing the frequency of gathering to only every 3 months.The purpose of this study was to examine the implementation of PKH in decreasing poverty in Bantang Village, Kintamani District, Bangli Regency. The study is using descriptive qualitative methods and collect data by mean of interviews or observation This study conclude that the program are successful in ensuring the fulfillment of children’s educational and medical need, but still not be able to drastically change the bad behavior of the adults. Keywords: Policy Implementation, Hope for Families Program